2016
DOI: 10.1158/0008-5472.can-16-1492
|View full text |Cite
|
Sign up to set email alerts
|

TRPA1 Mediates Aromatase Inhibitor–Evoked Pain by the Aromatase Substrate Androstenedione

Abstract: Aromatase inhibitors (AI) induce painful musculoskeletal symptoms (AIMSS), which are dependent upon the pain transducing receptor TRPA1. However, as the AI concentrations required to engage TRPA1 in mice are higher than those found in the plasma of patients, we hypothesized that additional factors may cooperate to induce AIMSS. Here we report that the aromatase substrate androstenedione, unique among several steroid hormones, targeted TRPA1 in peptidergic primary sensory neurons in rodent and human cells expre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…20 Notably, the synergistic action of clinically relevant concentrations of letrozole, androstenedione and ROS reproduced inflammatory and neuropathic pain in mice, similar to the musculoskeletal symptoms reported by breast cancer patients treated with aromatase inhibitors. 20 Cancer remarkably disrupts tissue architecture and alters the biochemistry and metabolism of the microenvironment. 21 Oxidative stress generation in cancer cells, 22 as well as in the cells surrounding the tumor, 8,23,24 is one of the most common and major changes associated with cancer growth.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…20 Notably, the synergistic action of clinically relevant concentrations of letrozole, androstenedione and ROS reproduced inflammatory and neuropathic pain in mice, similar to the musculoskeletal symptoms reported by breast cancer patients treated with aromatase inhibitors. 20 Cancer remarkably disrupts tissue architecture and alters the biochemistry and metabolism of the microenvironment. 21 Oxidative stress generation in cancer cells, 22 as well as in the cells surrounding the tumor, 8,23,24 is one of the most common and major changes associated with cancer growth.…”
Section: Introductionmentioning
confidence: 70%
“…Furthermore, TRPA1 activation by two channel agonists, the aromatase inhibitors, letrozole and the aromatase substrate, androstenedione, was exaggerated by ROS . Notably, the synergistic action of clinically relevant concentrations of letrozole, androstenedione and ROS reproduced inflammatory and neuropathic pain in mice, similar to the musculoskeletal symptoms reported by breast cancer patients treated with aromatase inhibitors …”
Section: Introductionmentioning
confidence: 72%
“…Contrary to the above, a positive role in TRPV1 activation by androstenedione has been recently reported. In this sense it was demonstrated that androstenedione activates currents in DRG neurons from the TRPA1 knockout mice and that these currents were inhibited by capsazepine [77], a TRPV1 antagonist, suggesting that these currents were due to TRPV1 activation, Table 1. It is interesting to note that some compounds used as treatments for breast cancer are based on their anti-estrogenic effects using compounds with similar structures to androstenedione and that they cause pain [78].…”
Section: Trpv1 Is Also Targeted By Androgensmentioning
confidence: 99%
“…Thus, a possible synergic effect between androstenedione and the aromatase inhibitors to produce pain was investigated. Whole-cell electrophysiological experiments carried out in HEK293 cells expressing the human TRPA1 channel showed that the application of androstenedione elicited inward currents, which were abolished by a selective TRPA1 blocker [77], Table 1. It was also assayed in mouse DRG neurons, where androstenedione produced calcium influx partially dependent on TRPA1 since DRG neurons from TRPA1 knockout mice displayed residual currents which were abrogated by capsazepine, as was mentioned above [77].…”
Section: Trpa1: Estrogens and Androgens Regulate Its Expression And Fmentioning
confidence: 99%
“…13,21,22 Different from some chemotherapeutic agents that do not appear to directly stimulate TRPA1, 13,21,22 we showed that dacarbazine selectively activates TRPA1 when evaluated in human TRPA1-HEK293 cells and cultured mouse DRG neurons, a response abolished by TRPA1 antagonist HC-030031. The dacarbazine action is like that observed for aromatase inhibitors, exemestane, letrozole and anastrozole; and the aromatase substrate androstenedione, 35,36 which were able to directly activate the TRPA1 causing pain conditions. This evidence is derived from the observation that dacarbazine evoked calcium response in hTRPA1-HEK293 cells but not in naive cells, in which it was abolished by the selective TRPA1 antagonist HC-030031.…”
Section: Discussionmentioning
confidence: 74%